(untitled) (Journal of the College of Basic Education, 2024)
The poet’s creativity crystallizes according to his sense of incentives and external and vicious influences, as a motive for the poetic experience with its various purposes, and pride represents the flexible self and one of these purposes, the poets rode throughout the ages and times of his vehicle to praise the poet, The other, except that the recipient of poetry is in When the modern sects and Almoravids travel from description, praise, and flirtation to pride, they find themselves as if they traveled from the depths to the shallows. Because of the lack of pride compared to others. The reason for choosing the topic lies in the absence of an independent study on self-pride in these two Andalusian eras, as far as we know, which required us to delve into the depths of research into pride and its components, which varied according to the motives that led the poets to say, as in other eras, and included pride in courage. Strength, patience, self-esteem, lineage, pride in poetry, science, and the arts, and refraining from satire. It is worth noting that the study chose the descriptive analytical method as a path to follow in analyzing texts and revealing their features, motives, and aesthetics. The research was divided into an introduction, elements of pride, a conclusion, and a list of sources and references.